Association of childhood trauma with cognitive domains in adult patients with mental disorders and in non-clinical populations: a systematic review - Rosa, Melissa; Scassellati, Catia; Cattaneo, Annamaria (Frontiers in Psychology, 2023)
Although the association between cognitive performances and the onset of psychiatric disorders has been widely investigated, limited research on the role of childhood trauma or early life stress (CT/ELS), and whether this role differs between clinical and non-clinical cohorts is available. This systematic review aims at filling this gap, testing whether the occurrence of CT/ELS and its subtypes are associated with cognitive domains (general cognitive ability, executive functions, working memory, attention, processing speed, verbal/visual memory) in patients with psychiatric disorders and in non-clinical populations. This study followed the PRISMA 2020 guidelines and the Newcastle-Ottawa scale for quality assessment. The search was performed until May 2022. Seventy-four studies were classified as eligible. The graphical representations of the results reported an association between exposure to CT/ELS and worse general cognitive ability, verbal/visual memory, processing speed and attention in patients affected by anxiety, mood and psychotic disorders, and that specific CT/ELS subtypes (physical neglect, physical/sexual abuse) can differentially influence specific cognitive abilities (executive functions, attention, working memory, verbal/visual memory). In non-clinical cohorts we found associations between CT/ELS exposure and impairments in executive functions, processing speed and working memory, while physical neglect was related to general cognitive ability and working memory. Concerning the emotional abuse/neglect subtypes in both populations, the results indicated their involvement in cognitive functioning; however, the few studies conducted are not enough to reach definitive conclusions. These findings suggest an association of CT/ELS with specific cognitive deficits and psychopathology.